Effect Of Cryorolling On The Microstructures, Mechanical Properties And Corrosion Behaviour Of Low Carbon Steel Using Martensite Starting Microstructure - Ahmad, Muhammad Syafiq (2020)
The properties of low carbon steel are often tailored to suit specific application through the manipulation of microstructure. The microstructural features including morphology, martensite volume fraction and grain size. Such microstructural features can be changed by adjusting the soaking time and temperature within intercritical zone during heat treatment. The present works aims to study the effect of intercritical annealing followed by cryorolling on the microstructure, mechanical properties and corrosion behavior of low carbon steel with 0.06 wt% C. Low carbon steel underwent intercritical annealing through intermediate quenching and step quenching technique at 750°C, 800°C, 830°C and 850°C with various soaking times (3, 5, 10 and 15 minutes) and followed by rolling at cryogenic temperature at 90% reduction. The details microstructural characteristics and mechanical properties of cryorolled low carbon steel were investigated using optical microscope (OM), X-ray diffraction (XRD), scanning electron microscope (SEM), Vicker microhardness and tensile test. A fibrous martensite morphology obtained from the intermediate quenched exhibits much better hardness compared to the blocky martensite morphology produced by step quenching treatment. A higher fraction of martensite volume and a much finer microstructure were obtained in intermediate quenched low carbon steel. Based on the hardness value (404.6 Hv), sample intercritically annealed via intermediate quenching process at 830°C (5 minutes) was chosen for different thickness reduction (50%, 70% and 90%) analysis. Hardness and tensile strength showed an increasing value with increasing percentage reduction, and the highest value obtained at 90% reduction with 429.4 Hv and 1537 MPa, respectively. The cryorolled sample at 90% reduction has the smallest crystallite size (13.70 nm) and highest lattice strain (74.6 x 10-3). Corrosion resistance decreases with thickness reduction, and the highest corrosion rate attained at 90% reduction with 5.968 mm/year.